Knowledge, beliefs and practices of dietitians and doctors in South Africa on the use of the internet in healthcare - Najaar, Baheya (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--University of Stellenbosch, 2009.